Caracterização de organizações autônomas descentralizadas - VELOSO, Alan Tony Souza (2019)
The concept of Decentralized Autonomous Organization (DAO) has emerged as an organization that can operate without a managerial hierarchy, that is, autonomous. This concept was made possible by blockchain technology, and for this reason, was restricted to it. Although the blockchain studies are constantly advancing, some concepts linked to it still cause doubts. When decoupling DAO from blockchain, it ceases to be the study of an area and becomes an area of study, for that, a survey of its characteristics and its association with already established concepts is necessary. The identification and understanding of these characteristics of DAO, in a clear and objective way, generating their characterization, was the main objective of this work. This characterization is relevant both for its analysis and for its development. By relating the DAO concept to established concepts, we can diversify and cover a greater number of DAO studies. In order to achieve these objectives, this work proposes to characterize DAO through the domain analysis, to define it in a way not to limit to a specific technology, susceptible of obsolence, correlating the characteristics to the concepts of Multiagent Systems and Decentralized Organizations. For the development of this work, we used a method of domain analysis that was free of implementation aspects, more precisely, the Feature-Oriented Domain Analysis Method (FODA), in which we obtained the main characteristics. In terms of these characteristics, we analyze them in order to integrate them and, finally, generate a free definition of technological aspects.